Implementasi Manajemen Keuangan Sekolah Dalam Pemenuhan Sarana Dan Prasarana Pendidikan - Masbullah Masbullah; Amru Bin As; Naili Mudzafaroh; Ahmad Hariyadi; Defi Dachlian Nurdiana (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2023)
This study aims to determine how the implementation of school financial management in the fulfillment of educational facilities and infrastructure at SMA Negeri 1 Puri which focuses on planning and implementing school financial management in fulfilling educational facilities and infrastructure at SMA Negeri 1 Puri Mojokerto. This study uses a qualitative approach with descriptive analysis with the research sub-genres including the principal, school treasurer and waka in the field of facilities and infrastructure. The data collection techniques used were interviews, observations, and documentation studies. The validity of the data was tested by triangulation of sources and techniques. The data obtained were analyzed through data reduction, data presentation, and data verification. The results of the research show that the process of planning and implementing finances in fulfilling educational facilities and infrastructure at SMAN 1 Puri has been carried out optimally, as evidenced by the availability of educational facilities and infrastructure in accordance with the provisions regarding high school facilities and infrastructure standards. Financial management is carried out using the principles of transparency and public accountability.